PERENCANAAN DAN PERANCANGAN TAMAN WISATA KULINER DI KABUPATEN ENREKANG - Burhanuddin, Burhanuddin; Rahman, St Aisyah; Sakinah, Intan (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2017)
Abstrak_ Potensi kuliner Kabupaten Enrekang menjadi perhatian pemerintah terhadap pengembangan pariwisata sangat besar terutama pada jalur menuju Tanatoraja. Maka diperlukan sebuah perancangan taman wisata kuliner di Enrekang. Metode yang digunakan ialah metode desktriptif melalui studi literatur, studi preseden, dan studi lapangan dengan melakukan survey langsung ke lapangan untuk mengamati dan menganalisis lingkungan sekitar tapak. Perancangan menggunakan konsep Arsitektur Kontemporer berupa konsep perancangan dalam merancang kawasan taman wisata kuliner, terdiri dari: zoning/ peruntukan lahan (land use), bentuk dan massa bangunan (building from and massing), sirkulasi dan parkir (circulation and parking), jalur pejalan kaki (pedestrian ways), ruang terbuka (open space), dan penanda (signage).Kata kunci : Wisata Kuliner, Konsep Koneporer, Enrekang. Abstract_Culinery’s Potency in Enrekang Regency is the government's attention to the enormous tourism development especially on the path to go to Tanatoraja. In this case, it is needed a design of culinary tourism area in Enrekang. The method used is descriptive method through literature study, precedent study, and field study by conducting direct survey to the field to observe and analyze the environment around the site. The design using the concept of Contemporary Architecture includedof design concept in designing culinary tourism area, consists of: zoning / land use (land use), shape and building mass (building from and massing), circulation and parking (circulation and parking), pedestrian path (pedestrian ways), open space (space), and signage (signage).Keywords: Culinary Tour, Concept of Koneporer, Enrekang.